Flipped FAR730 - Abd Rahman, Nurulhuda (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Islamic accounting knowledge extends beyond conventional accounting by aiming to achieve success both in this world and the hereafter. Changes in teaching approaches require focus and adaptation to accommodate learners with different learning styles, especially for postgraduate students who are expected to take greater responsibility for their own learning, engage in specialized and advanced research, and demonstrate high levels of critical thinking and independent work. Flipped learning is an effective approach for postgraduate students as it enhances engagement and comprehension. The flipped learning ecosystem requires high-quality pre-class learning materials, collaborative platforms, and active learning techniques. Moreover, flipped learning in a complex subject such as Islamic accounting is considered an innovative teaching method because it flips the traditional roles of teacher and student, fosters active learning, and integrates Islamic values into a student's character and personal development. This innovative approach not only enriches students' academic experience but also equips them with the practical skills and ethical framework necessary for success in the growing Islamic finance and accounting sectors, opening new career and business opportunities in both local and global markets.